Impact of integrated management on the development of Tarekat Tasawuf in Negeri Sembilan, Malaysia / Mohammad Fahmi Abdul Hamid and Ishak Sulaiman - Abdul Hamid, Mohammad Fahmi; Sulaiman, Ishak (Universiti Teknologi MARA, Perlis, 2017)
Tarekat tasawuf has long been established in Malaysia including in Negeri Sembilan. Tarekat has been introduced in this state since 1900. However, at the early stage, there was no systematic and integrated management system that had been implemented. This article discusses the impact of integrated management on the development of tarekat tasawuf in Negeri Sembilan. Methodologies involved in this study include literature review, analysis of related documents and personal communication with the Registrar of Tarekat Tasawuf Jabatan Mufti Kerajaan Negeri Sembilan. The objective of this study is to examine the efficiency of tarekat management and its impact on the development of tarekat tasawuf in Negeri Sembilan. Establishment of Bahagian Tarekat Tasawuf Jabatan Mufti Kerajaan Negeri Sembilan in 2007 proves that the state government is very serious in regulating all tarekat activities in this state. The existence of the Enakmen Tarekat Tasawuf Negeri Sembilan 2005 which came into force in 2006 also played an important role as a policy used by the management to run the registration process of tarekat, the regulation control, investigation procedures and cancellation of the approval status of problematic tasawuf. The involvement of a qualified and authoritative academic Jilsah al-Turuq alSufiyyah also strengthens the management of tarekat tasawuf in this state. The result of integrated and systematic management shows the positive development of tarekat tasawuf in Negeri Sembilan. A total of 12 tarekat tasawuf have been legally registered and monitored by the Bahagian Tarekat Tasawuf Negeri Sembilan. Based on the latest registration recorded in 2017, there is no new addition of tarekat until todate. The existence of tarekat practicing center in Negeri Sembilan was plotted to see the distribution and centralization of tarekat centers which clearly show that Seremban is the highest in the number of tarekat practicing centers. This is likely to be related to the position of the Jabatan Mufti Negeri Sembilan that is in Seremban. Efforts undertaken by the Jabatan Mufti Kerajaan Negeri Sembilan will hopefully be emulated by other states in Malaysia in order to ensure the spreading of tarekat tasawuf coincides with Islamic law and the principles of the al-Quran and al-Sunnah and far from deviation of faith